A Thorough Systematic Review of the Connection Between Acid Reflux and Laryngomalacia - Budi, Agus; Farida (International Medical Journal Corp. Ltd, 2024)
Background: Reflux is frequently associated with laryngomalacia, a common upper airway disorder in children that affects 4%–20% of patients. Damage from reflux weakens the supraglottic tissues, obstructing the airway and preventing growth. Methods: Following PRISMA 2020 guidelines, this systematic review concentrated on full-text English literature published between 2014 and 2024. Editorials and review articles that appeared in the same journal as the submission were not accepted without a DOI. The literature was assembled using a variety of online resources, including ScienceDirect, PubMed, and SagePub. Result: Following a rigorous three-stage screening procedure, six papers were found to have relevant links to our current extensive investigation. After that, the entire text was carefully examined, and these particular sections got extra focus. Conclusion: Studies have shown that laryngomalacia, a condition characterized by acid reflux, has a significant role in the condition, with pepsin serving as a comorbidity. However, the efficacy of acid-targeting medications remains unclear.